The β-mixing rate of STIT tessellations. Issue 3 (2nd April 2016) - Martínez, S.; Nagel, W.
Abstract : We consider homogeneous STIT tessellations in the -dimensional Euclidean space and show that the (spatial) -mixing rate converges to zero.